The Metamorphosis of the Hero: Principles, Processes, and Purpose - Allison, Scott T.; Goethals, George R.; Marrinan, Allyson R.; Parker, Owen M.; Spyrou, Smaragda P.; Stein, Madison (Frontiers in Psychology, 2019)
This article examines the phenomenon of heroic metamorphosis: what it is, how it unfolds, and why it is important. First, we describe six types of transformation of the hero: mental, moral, emotional, spiritual, physical, and motivational. We then argue that these metamorphoses serve five functions: they foster developmental growth, promote healing, cultivate social unity, advance society, and deepen cosmic understanding. Internal and external sources of transformation are discussed, with emphasis on the importance of mentorship in producing metamorphic growth. Next we describe the three arcs of heroic transformation: egocentricity to sociocentricity, dependence to autonomy, and stagnation to growth. We then discuss three activities that promote heroic metamorphosis as well as those that hinder it. Implications for research on human growth and development are discussed.